2017
DOI: 10.1186/s12906-017-1815-z
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity, toxicity and anti-inflammatory potential of methanolic extracts of four ethnomedicinal plant species from Punjab, Pakistan

Abstract: BackgroundThe plant species Aristolochia indica (AI), Melilotus indicus (MI), Tribulus terrestris (TT) and Cuscuta pedicellata (CP) are widely used in folk medicine in the villages around Chowk Azam, South Punjab, Pakistan. The aim of this study was to evaluate the antioxidant activity, phytochemical composition, and the antibacterial, antifungal, cytotoxic and anti-inflammatory potential of the four medicinal plants listed above.For CP stem, this study represents (to the best of our knowledge) the first time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 30 publications
8
46
0
2
Order By: Relevance
“…Crude extracts of herbs, cereals, fruits, vegetables and other plant materials rich in phenolics are being used increasingly in the food industry because they retard oxidative degradation of lipids, thereby improving the quality and nutritional value of food [ 58 ]. The methanol extract had the highest TPC, with the residual aqueous fraction containing much lower levels of phenolics, which is in agreement with other reports [ 59 , 60 ]. Phenolic compounds are known to donate hydrogen to reduce oxidative damage by detoxifying free radicals [ 61 , 62 ].…”
Section: Resultssupporting
confidence: 93%
“…Crude extracts of herbs, cereals, fruits, vegetables and other plant materials rich in phenolics are being used increasingly in the food industry because they retard oxidative degradation of lipids, thereby improving the quality and nutritional value of food [ 58 ]. The methanol extract had the highest TPC, with the residual aqueous fraction containing much lower levels of phenolics, which is in agreement with other reports [ 59 , 60 ]. Phenolic compounds are known to donate hydrogen to reduce oxidative damage by detoxifying free radicals [ 61 , 62 ].…”
Section: Resultssupporting
confidence: 93%
“…In addition, for these five bacteria, except V. parahaemolyticus, CPEE exhibited higher antibacterial activity compared to CPWE. These results may be attributed to the higher polyphenol content detected in CPEE (Table 2), which is also consistent with previous findings [50]. Interestingly, for V. parahaemolyticus, CPEE had less antibacterial activity compared to CPWE.…”
Section: Analysis Of Phenolic Compound Composition Storagesupporting
confidence: 91%
“…The ethanolic extract of Oryza sativa inhibited the egg albumin and bovin serum denaturation by 84.15% 60.47%, respectively [ 36 ]. The methanolic stem extract of Cuscuta pedicellata also exhibited strong inhibition of protein denaturation [ 43 ]. Kamble et al [ 44 ] indicated that ethanolic extract of leaves of Vitex negundo and Punica granatum showed potential anti-arthritic activity as compared to aqueous extract.…”
Section: Resultsmentioning
confidence: 99%